2018
DOI: 10.1111/nep.13075
|View full text |Cite
|
Sign up to set email alerts
|

Loss of appendicular muscle mass in haemodialysis patients is associated with increased self‐reported depression, anxiety and lower general health scores

Abstract: We report an association between ALM index measured by segmental bioimpedance and increased self-reported depression, anxiety and decreased general health. Whether treatment programs designed to improve muscle mass, can lead to reduced levels of depression, and anxiety and improved perceived general health, remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…As part of UK National Health Service guidelines to request patient feedback on treatment received, all patients attending for routine outpatient dialysis treatments under the care of a university hospital were asked to complete a questionnaire recording the frequency of dialysis-associated symptoms and time to recovery using a previously reported visual analogue scale [4,14], and also a distress thermometer score, a screening tool for assessing psychological stress [19]. Hospital-computerised medical records were reviewed to obtain co-morbidity which had been recorded according to the Stoke-Davies grading [20] and frailty using the Canadian geriatric frailty score [21].…”
Section: Methodsmentioning
confidence: 99%
“…As part of UK National Health Service guidelines to request patient feedback on treatment received, all patients attending for routine outpatient dialysis treatments under the care of a university hospital were asked to complete a questionnaire recording the frequency of dialysis-associated symptoms and time to recovery using a previously reported visual analogue scale [4,14], and also a distress thermometer score, a screening tool for assessing psychological stress [19]. Hospital-computerised medical records were reviewed to obtain co-morbidity which had been recorded according to the Stoke-Davies grading [20] and frailty using the Canadian geriatric frailty score [21].…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the prevalence of SARC-F ≥4 was higher among hemodialysis patients than among the general community-dwelling elderly population [12][13][14]. Patients with chronic kidney disease are more likely to experience greater muscle loss and decreased physical function, termed sarcopenia, because of a combination of multiple factors, including metabolic acidosis, vitamin D deficiency, insulin resistance, anemia, reduced physical activity, testosterone deficiency in men, protein losses with dialysis, dietary restrictions, and depression [7,8,29]. Moreover, in the present study, the prevalence of SARC-F ≥4 increased with age, comorbidities, depressive symptoms, and frailty, in agreement with the findings of previous studies [12,13,15,30].…”
Section: Discussionmentioning
confidence: 55%
“…Sarcopenia may be more severe among vulnerable populations, such as those with end-stage renal disease. In hemodialysis patients, the prevalence of sarcopenia was reported to be between 12.7% and 33.7% [4][5][6], and those with sarcopenia have an increased risk of fractures, anxiety, depression, cardiovascular complications, and mortality [4,[7][8][9]. Therefore, early identification and interventions for hemodialysis patients with sarcopenia are essential for effective disease management.…”
Section: Introductionmentioning
confidence: 99%
“…However, as our home HD patient numbers had fallen from 21 in 2015 to 8 in 2019, we reviewed our shared-care policy. [6][7][8] However, previous studies have reported that older more co-morbid dialysis patients report less depression and lower distress thermometer scores than younger healthier patients, 24 and older patients generally have lower dietary intake, which may account for no differences in potassium or phosphate control. As probably expected, patients who performed shared-HD care were younger, had lower frailty 16 and functional Karnofsky scores 17 and less co-morbidity including diabetes, 18 and were physical stronger compared to those who were dependent upon the dialysis center staff.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there were no differences in potential markers of compliance with dietary restriction in terms of potassium and phosphate control, or volume control as assessed by NTproBNP and fluid removal on dialysis, which would appear to contradict Orem's self-care model and other psychological theorems which have suggested that patients who take greater care of their own medical care have less depression, and are more motivated to perform and promote activities designed to maintain improve health care. [6][7][8] However, previous studies have reported that older more co-morbid dialysis patients report less depression and lower distress thermometer scores than younger healthier patients, 24 and older patients generally have lower dietary intake, which may account for no differences in potassium or phosphate control. 25 Dialysis sessions, dialysis adequacy, ultrafiltration rates, changes in blood pressure during dialysis, and frequency of symptomatic intra-dialytic hypotension requiring nursing interventions did not differ.…”
Section: Discussionmentioning
confidence: 99%